Kajian Etnobotani Pakundalang (Blumea balsamifera (L.) DC.) sebagai Solusi Alternatif untuk Kemandirian Kesehatan Masyarakat Banggai Kepulauan, Sulawesi Tengah - Wardah Wardah; Emma Sri Kuncari (The Ethnobiological Society of Indonesia, 2020)
Banggai Kepulauan Regency (Bangkep) is a small and outermost island in Indonesia, has problems with slow access to and from outside due to inadequate transportation and telecommunications facilities. Therefore, people's dependence on natural resources around them, especially medicinal plants, is essential. The method used in this study was selected interviews with village heads, traditional leaders, shamans, traditional healers, and villagers who use plants as medicinal ingredients. The results of study carried out in several villages in Banggai Kepulauan Regency showed that the community still use plant resources that are growing around to treat various ailments. One type of plant that is widely used as a medicinal ingredient is pakundalang (Blumea balsamifera (L.) DC.) which belongs to the Asteraceae family. Pakundalang is an alternative solution for community health independence to overcome various ailments including postpartum treatment, fever, flu, pain during menstruation, hemorrhoids, internal wounds, skin pain, cough, high blood pressure, diarrhea, rheumatism, stomach pain, diabetes, shortness of breath, heartburn, and malaria. Data and information regarding the ethnobotany of pakundalang are discussed in this article.